2020
DOI: 10.3390/su12041567
|View full text |Cite
|
Sign up to set email alerts
|

Compaction Process as a Concept of Press-Cake Production from Organic Waste

Abstract: As a result of agri-food production large amounts of organic waste are created in the form of press cakes. Until now, they were mainly used as animal fodder and also utilized for biofuels production. No other way usage has been found yet. A large quantity of these by-products is usually discarded in open areas, which leads to potentially serious environmental problems. The rich chemical composition of these waste products makes it possible to use them for producing other food products valuable for consumers. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
5
9
0
Order By: Relevance
“…The parameter is too important to neglect its impact on foaming and apparent density of the final products. Therefore, the experimental investigation showed that the original moisture content of SFP filler particles was 8.4 ± 0.3 wt.% and it confirms the results obtained in other studies [ 31 , 32 ], i.e., up to 11 wt.%. However, after the thermal treatment at 110 °C, the moisture content was reduced to 1.1 ± 0.2 wt.%.…”
Section: Resultssupporting
confidence: 89%
“…The parameter is too important to neglect its impact on foaming and apparent density of the final products. Therefore, the experimental investigation showed that the original moisture content of SFP filler particles was 8.4 ± 0.3 wt.% and it confirms the results obtained in other studies [ 31 , 32 ], i.e., up to 11 wt.%. However, after the thermal treatment at 110 °C, the moisture content was reduced to 1.1 ± 0.2 wt.%.…”
Section: Resultssupporting
confidence: 89%
“…When coated with starch and enriched with honey, they have better hardness and resistance to cutting. These tablets can be directly consumed if coated with various flavors as chocolate or caramel [77].…”
Section: Applications In Food Productsmentioning
confidence: 99%
“…Sunflower press cake particles can be considered as another promising filler. Some studies have shown that they could be successfully utilised as animal nutrition due to high amounts of protein, hemicellulose, and cellulose, as a fertilizer that contains minerals such as Mg, Ca, Fe, P, and Mn, or for energy purposes [ 9 ]. However, the literature also indicates that the application of oil-based press cakes as food for humans or animals is limited due to anti-nutritional factors [ 10 ].…”
Section: Introductionmentioning
confidence: 99%